Psychosocial characteristics and motivational factors in woman seeking cosmetic breast augmentation surgery - Nikolić, Jelena Ratko; Janjić, Zlata Marko; Marinković, Marija; Petrović, Jelica Dragan; Božić, Teodora Miloš (Vojnosanitetski pregled, 2017)
Background/Aim. There are various opinions regarding the factors motivating women to undergo breast augmentation. The aim of this study was to estimate motivation for augmentation mammaplasty (AM), self-esteem and body image perception in breast augmentation patients. Methods. This prospective study involved AM patients operated in the Clinical Center of Vojvodina during a 3-year period. A total of 45 patients responded to our package of questionnaires designed to assess motivation for surgery, self-esteem level and body image perception. Those patients were compared to the control group of women who did not want to change their breast size, and who were similar in their age, social status and education level. Our package of questionnaires included a general questionnaire, Photographic Figure Rating Scale (PFRS) and Rosenberg’s Self-Esteem Scale. Results. Differences in marital status, educational level, habitation and employment status were statistically insignificant, but there was a significantly lower body mass index (BMI) in the operated women. Considering motives for surgery, a few factors were distinguished: desire to feel more feminine (82.2%), confident (75.5%) and attractive (73.3%), to feel less shy with men (64.4%), to improve their sex life (46.5%), teasing history (42.2%) and easier to find a partner (11.1%) and job (2.2%). Both groups demonstrated a high self-esteem level, but in the the AM group results were lower than in the control group. The mean current self-rating by the PFRS in the group AM was lower than in the control group (4.28 ± 1.3 vs 5.12 ± 1.23, respectively) and this coincided with lower BMI in the AM group. The women in the AM group had chosen significantly smaller body size as maximally attractive, and had chosen a narrower attractive body size range than the women in the control group. Conclusion. Preoperative evaluation of patients’ motives for surgery can help surgeons to exclude woman with unrealistic expectations and different psychological problems.
Keywords: esthetics; mammaplasty; psychology; personality assessment; questionnaires